P-OGC16 Minimally Invasive Oesophagectomy: Technique and learning curve over 10 years. (16th December 2021) - May-Miller, Peter; MacKenzie, Hugh; Jenkins, Nick; Mercer, Stuart; Carter, Nick; van Boxel, Gijs; Knight, Ben
Abstract: Background: The use of minimally invasive oesophagectomy (MIO) in the treatment of patients with oesophageal malignancy has developed since its first description by Cuschieri in 1992, although mainstream uptake of this technique has not been forthcoming. Oncological resection margins were not compromised in MIO, whilst complications and two-year mortality rates improved in MIO compared to open oesophagectomy. The advantages of MIO compared to open surgery include the speed of recovery, improved return to baseline quality of life, better physical function and less pain. We present our experience of MIO including operative technique, tips, and learning curve. Methods: 160 patients underwent MIO at Portsmouth Hospitals University NHS Trust between August 2010 and December 2019. After June 2016 there was a significant change in surgical technique and pathway as outlined below and this time point has been interrogated. Primary outcomes were operative duration (minutes) and both 30-day and in-hospital mortality. Secondary outcomes were length of in hospital stay (days), ITU stay, conversion to open surgery and complications. We undertake laparoscopic abdominal phase and thoracoscopic or robotic assisted thoracic phase oeasophagectomy. Dual consultant operating is standard; and we work consistently with the same group of anaesthetists and theatre staff. Results: 82.5% of our 160 patients were male, median age was 67 years. Operative duration showed a steep learning curve over the first 10 cases followed by stabilisation to case 56 and then improvement. CUSUM analysis of the anastomotic leaks showed a change point at 53 cases - 30.8% vs 16.7% (p = 0.05). 30-day mortality is 1.88% and median length of stay 12 days (IQR12.75). Complications of Clavien-Dindo ≥III occurred in 35% and "perfect" outcomes in 21.25%. Conversion to open in 5.6% of cases but only 1 in the last 100 patients. Conclusions: There is a learning curve associated with the adoption of a new technique. MIO can be performed safely and cost effectively with equivalent oncological outcomes with the advantage of improved quality of life. Oesophageal cancer is still poorly understood and we therefore must spend more thought on how best to give our patients good quality disease free life. Our outcome data is within existing published data and our prospectively collected data is thorough and meticulous. Though some complications are inevitable, small changes lead to marginal gains and add up to better outcomes.